Advantages of mRNA Amplification for Microarray Analysis - A.L. Feldman; N.G. Costouros; E. Wang; M. Qian; F.M. Marincola; H.R. Alexander; S.K. Libutti (BioTechniques)
Expanding applications of cDNA microarrays such as fine needle aspiration biopsy and laser capture microdissection necessitate the ability to perform arrays with minute starting amounts of RNA. While methods for amplifying RNA have been advocated, the fidelity of array results using amplified material has not been fully validated. Here we demonstrate preserved fidelity in arrays using one or two rounds of mRNA amplification, validated by downstream real-time quantitative PCR. In addition, the quality of the array data was superior to that obtained using total RNA. Based on these results, we recommend routine mRNA amplification for all cDNA microarray-based analysis of gene expression.